Criteria for Assessing Students’ Independent Creative Work in Specialized Art Schools - Xasanova Sitora Shuhrat qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ANNOTATION: This article examines the criteria for evaluating students’ independent creative work in specialized art schools. It emphasizes the importance of objective and structured assessment methods that consider not only technical skills but also creativity, originality, and personal expression. The study highlights how clear assessment criteria enhance student motivation, foster artistic growth, and promote critical self-reflection. Drawing on the research of S.A. Shovdirov and other contemporary scholars, the article analyzes effective approaches to assessing independent artistic projects, including formative and summative evaluation strategies. It also discusses the balance between evaluating process-oriented skills and the final artistic product to ensure a holistic understanding of student achievement in art education.